Effect of Co-channel Interference in MARC System - Karabulut, Muhammet Ali; Ilhan, Haci (IEEE, 2017)
In this study, the error performance analysis of decode and forward (DF) based multiple access relay channel (MARC) system model is investigated for binary phase shift keying (BPSK) modulation when there is co-channel interference effects at relay node and maximum likelihood (ML) approach is used at destination node. MARC system model is one of the important network coding applications in wireless cooperative communication. The simulation results show that MARC system model provides full diversity gain for BPSK modulation.
Keywords: co-channel interference; network coding; multiple access relay channel; COOPERATIVE DIVERSITY; Acoustics; Computer Science; Engineering; Telecommunications